A high fat diet containing saturated but not unsaturated fatty acids enhances T cell receptor clustering on the nanoscale. (September 2015) - Shaikh, Saame Raza; Boyle, Sarah; Edidin, Michael
Abstract: Cell culture studies show that the nanoscale lateral organization of surface receptors, their clustering or dispersion, can be altered by changing the lipid composition of the membrane bilayer. However, little is known about similar changes in vivo, which can be effected by changing dietary lipids. We describe the use of a newly developed method, k-space image correlation spectroscopy, kICS, for analysis of quantum dot fluorescence to show that a high fat diet can alter the nanometer-scale clustering of the murine T cell receptor, TCR, on the surface of naive CD4 + T cells. We found that diets enriched primarily in saturated fatty acids increased TCR nanoscale clustering to a level usually seen only on activated cells. Diets enriched in monounsaturated or n-3 polyunsaturated fatty acids had no effect on TCR clustering. Also none of the high fat diets affected TCR clustering on the micrometer scale. Furthermore, the effect of the diets was similar in young and middle aged mice. Our data establish proof-of-principle that TCR nanoscale clustering is sensitive to the composition of dietary fat.